Cover Feature: Asymmetric Direct/Stepwise Dearomatization Reactions Involving Hypervalent Iodine Reagents (Chem. Asian J. 4/2022). Issue 4 (14th February 2022) - Kumar, Ravi; Singh, Fateh V.; Takenaga, Naoko; Dohi, Toshifumi
Abstract : Cyclic unsaturated ketone frameworks, which are obtained as the dearomatized products of phenols and their derivatives, are valuable to the synthesis of complex molecules and also contribute to the generation of products that can be readily employed for further transformations. Herein, the use of hypervalent iodine compounds to access enantioenriched compounds through direct and stepwise dearomatization reactions have been elaborated. More information can be found in the Review by Ravi Kumar, Fateh V. Singh, Naoko Takenaga, and Toshifumi Dohi.